Phantom Limbs: Review of Chez, Victorian Dogs, Victorian Men: Affect and Animals in Nineteenth-Century Literature and Culture - Margini, Matt (Humanimalia, 2018)
Keridiana W. Chez, Victorian Dogs, Victorian Men: Affect and Animals in Nineteenth-Century Literature and Culture. The Ohio State University Press, 2017. 212 pp. $69.95